The design and application of a fixator for abdominal drainage tubes (一种腹腔引流管用固定器的设计与应用) - LIU Jieping (刘杰平); ZHENG Chenyuan (郑晨园); LIU Fuyan (刘夫艳); ZHAO Yufei (赵雨菲) (中西医结合护理)
Abdominal drainage tubes are commonly used drainage devices in clinical practice, and they play a vital role in reducing peritoneal effusion and preventing infection after surgery. Effective fixation is essential for ensuring smooth drainage of the drainage tubes. However, traditional fixation methods often face challenges such as unstable fixation, easy displacement and increased risk of infection. This paper introduced the design and application of a new type of fixator for abdominal drainage tubes. By connecting the drainage tube and the bandage, the bandage is fixed properly at the waist by elastic bands. The external protection and anti-pull clamping of the drainage tube are provided through the fixator, avoiding the occurrence of compression and closure of the drainage tube, and improving the fixation effect and usage safety of the drainage tube after surgery. (腹腔引流管是临床上常用的引流装置, 在术后减轻腹腔积液和预防感染方面发挥着重要作用。然而, 传统的引流管固定方式存在诸多不足, 如固定不牢、易移位以及感染风险增加等。本研究设计一种新型腹腔引流管用固定器。该固定器通过引流管与敷带的结合进行固定, 敷带利用松紧带缠绕固定于腰部, 同时固定管对引流管提供外部防护并实现防拉夹紧, 能有效避免引流管受压闭合的情况发生, 对提高术后引流管的固定效果和使用安全性, 以及改善患者的舒适度有积极作用。)